Controls on timing of exhumation and deformation in the northern Peruvian eastern Andean wedge as inferred from low‐temperature thermochronology and balanced cross section. Issue 4 (21st April 2015) - Eude, Adrien; Roddaz, Martin; Brichau, Stéphanie; Brusset, Stéphane; Calderon, Ysabel; Baby, Patrice; Soula, Jean‐Claude
Abstract In northern Peru, a 500 km long regional balanced section has been constructed across the eastern Andean wedge, using fieldwork, industrial seismic sections, and wells. The structure is characterized by a thin‐skinned thrust system involving the Eastern Cordillera (EC), the sub‐Andean zone (SAZ), and the Marañón foredeep. In the SAZ and the easternmost foredeep the development of the thrust system has been driven by the combination of two structural events. Permian thrust faults had been reactivated to form a basement duplex underlying the SAZ and the foredeep. At the same time a Triassic‐Jurassic extensional basin has been transported as a crustal ramp anticline on to the duplex roof fault, giving rise to the EC. The impingement of the EC was responsible for the deformation of the SAZ and the propagation of the thrust wedge. The minimum shortening calculated is 142 km, representing a shortening strain of ~ −28%. A sequential restoration calibrated by (U‐Th)/He and Fission Track dating on apatites and vitrinite reflectance values shows that shortening rates vary from 7.1 mm yr−1 between 17 and 8 Ma to 3.6 mm yr−1 between 8 Ma and today and suggests that the thrust wedge commenced propagation between 30 and 24 Ma. When compared with other Andean thrust wedges, we suggest that the timing of the thrust wedge propagation is not a simple function of the distance to the hinge of the Bolivian orocline and the propagation is not controlled by the precipitation regime. We rather suggest that reactivated basement faults favored thrust wedge propagation.